Iran Oil : The New Middle East Challenge to America - Howard, Roger (London I.B. Tauris, 2007)
The US sees itself as being locked into a confrontation with Iran, its number one enemy since the invasion of Saddam Hussein's Iraq. This book argues that by attempting to isolate Iran, the US may in fact be undermining its own power
Include Note and Index
Keywords: Petroleum reserves -- United States -- Iran -- Diplomatic relations